Enhanced transient oscillations-free response for a dual-active-bridge series-resonant DC-DC converter with dynamic trajectory prediction modulation - Shengzhi Zhou; Jiahua Tang (Heliyon)
The dual-active-bridge series-resonant converter, offering galvanic isolation and high power density, is a viable and attractive solution for the isolated DC/DC power stage in Solid-State Transformers. Under the step load commands, the resonant tanks typically experience severe oscillations, which delay the transient response and the entry into the final steady state. To address these drawbacks, this paper proposes a dynamic trajectory prediction modulation (DTPM) method for adjusting the transient process. State-plane analysis is used to describe the behavior of the resonant converter with single-phase-shift modulation. Subsequently, perturbation analysis is used to predict the impact of switching intervals on the state trajectory. Based on this analytical foundation, the proposed DTPM method regulates pulse widths and instantly adjusts the switching period during the transient state. The DTPM method swiftly regulates the transferred power, significantly reduces the oscillations in the resonant tank, and reduces computational burdens to facilitate digital implementation. The proposed modulation is validated by simulation and experimental results from an experimental prototype converter.